Nutritional status and socioeconomic level of schoolchildren aged 7 to 9 from Ciudad Obregon, Sonora - García-Jacobo, Silvia Grisel (Universidad de Sonora, 2019)
Introduction: The socioeconomic level is a determining factor of the health and lifestyle of the individual. Objective: Identify the relationship between the nutritional status and the socioeconomic level of schoolchildren aged 7 to 9 from Ciudad Obregon, Sonora. Methodology: Applied, quantitative, cross-sectional and correlational study; non-probabilistic sampling were used for convenience. The 2017 Socio-Demographic Questionnaire for parents was used. To assess the socioeconomic status, the AMAI-NSE8X7 Rule (2011 version) was applied, and anthropometric measures were taken to assess the nutritional status, using 3-97 percentile chart of the World Health Organization and Body Mass Index by age. The informed consent of parents and schoolchildren was obtained prior to its application. Results: It was applied to 114 schoolchildren, of which 53.5% were females, with a distribution by age group between 7, 8, and 9 years old (33.33%, 36.84%, and 29.82%, respectively). 41.1% of the schoolchildren from high socioeconomic status were overweight; a similar result from middle socioeconomic level schoolchildren (47.06%). Additionally, in low socioeconomic level schoolchildren normal nutritional status (30.9%) and obesity (30.7%) were detected. Conclusions: Three nutritional status were evenly distributed across the three socioeconomic levels; however, there is an important prevalence of overweight and obesity. Therefore, the need for guidance and monitoring from the primary education level stands out, so as to prevent the early onset of chronic degenerative diseases during adolescence or young adulthood.